Sticky information models in Dynare - Fabio Verona; Maik H. Wolters (Bank of Finland, 2013)
Macroeconomic models with sticky information include an infinite number of lagged expectations. Several authors have developed specialized solutions algorithms to solve these models under rational expectations. We demonstrate that it is also possible to implement this class of models in Dynare - a widely used software package for solving dynamic stochastic general equilibrium (DSGE) models. Using the Dynare macro language one can easily construct and change the required large number of lagged expectation terms. We assess the accuracy of simulations run with different truncation points for the lagged expectations terms and find that the solution is reasonably precise even for moderate truncation points.
URN:NBN:fi:bof-20140807607
Keywords: 330; sticky information; Dynare; macro-processor; lagged expectations